2013
DOI: 10.1179/1743285512y.0000000029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alumina on physical properties of an industrial zinc-copper smelting slagPart 1 – viscosity

Abstract: The rotating cylinder method was applied to measure the viscosities of an industrial iron silicate slag and mixtures of this slag with 5, 10 and 15 wt-% alumina addition, in temperature range 1100-1300uC. The measured viscosities were compared with the predicted values using two of the commercially available software products for viscosity calculations, namely ThermoslagH1?5 and FactSage TM 6?2. As the models can only predict viscosities for a solid free melt, obtained values by FactSage TM 6?2 were modified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Thus, how alumina is coordinated in the system is dependent on the base slag and the ratio of basic/acidic oxides in the system. The amphoteric behavior of alumina in melts, slags and glasses has been investigated quite broadly by measuring physical properties such as density, viscosity, surface tension, thermal and electrical conductivity [15][16][17][18]. As alumina influences the chemical and physical properties of the slags, naturally it has an influence on the minor element behavior, too.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, how alumina is coordinated in the system is dependent on the base slag and the ratio of basic/acidic oxides in the system. The amphoteric behavior of alumina in melts, slags and glasses has been investigated quite broadly by measuring physical properties such as density, viscosity, surface tension, thermal and electrical conductivity [15][16][17][18]. As alumina influences the chemical and physical properties of the slags, naturally it has an influence on the minor element behavior, too.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that as the SRM addition changes from 1 ton to 23 tons, the liquidus temperature of the slag decreases by 40°C. The decrease of the liquidus temperature and the increase of the viscosity could be related to the addition of Al 2 O 3 to the slag, as Mostaghel et al [14,15] reported in their study of the effect of the addition of Al 2 O 3 to slag after the fuming process in the Boliden-Rönnskär smelter. Additionally, the increase of the SiO 2 /Fe ratio could lead to a decrease of the liquidus temperature, as was stated by Hayes et al [9].…”
Section: Parameters Influencing Utilisation Of Srm In the Processmentioning
confidence: 83%
“…Similarly, work by Kang et al 16) using FactSage predicted a positive correlation but only at high mole fractions ( > 0.6). Conversely, KTH's Thermoslag, 18) showed a negative correlation.…”
Section: )mentioning
confidence: 86%
“…Some of the more famous frameworks in this area have been incorporated into proprietary software such as FactSage (developed by CRCT and GTT Technologies), 16,17) and ThermoSlag (developed by the Royal Institute of Technology (KTH)). 18) Comprising many different databases as well as frameworks, FactSage is an all-purpose thermodynamics software. It's sulphide capacity framework, developed by Kang and Pelton,16) is based on the extrapolation of all permutations of cations and anions on a pseudo-lattice.…”
Section: Short Range Ordermentioning
confidence: 99%